INNOVATIVE METHOD OF TRAINING FUTURE TEACHERS TO USE ELECTRONIC EDUCATIONAL RESOURCES IN THE CONTEXT OF DIGITALIZATION (World Conference on Agricultural and Earth Sciences, 2026)
This article discusses improving the quality of training graduates of educational institutions through the comprehensive use of electronic educational resources in combination with innovative forms and methods of teaching. The competent use of electronic educational resources, which involves the appropriate configuration of all components of the methodological teaching system, contributes to the formation of a holistic educational trajectory and, to a large extent, to the achievement of modern educational goals.
Keywords: electronic learning resources, intellectual potential, development, learning tool, fundamental knowledge, innovative learning.